Pediatric sonography - Siegel, Marilyn J. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"Pediatric Sonography, Fourth Edition gives you a complete working knowledge of the latest scanning technologies and the clinical applications of ultrasound in pediatric and adolescent patients. Readers will find just the guidance they need to determine the most appropriate imaging method for evaluating a specific clinical problem, conduct the sonographic examination, and interpret the findings. The book shows the sonographic appearance of normal anatomy and disease processes within each organ system and points out technical and interpretive artifacts and errors that can affect evaluations. This edition features more than 1,800 clear, sharp images, including over 300 full-color images throughout. Other highlights include discussions of the uses and limitations of mobile instrumentation and expanded coverage of ultrasound-guided interventional procedures"--Provided by publisher.
Physical principles and instrumentation / Nirvikar Dahiya, William D. Middleton, and Marilyn J. Siegel -- Ultrasound artifacts / William D. Middleton, Marilyn J. Siegel, and Nirvikar Dahiya -- Brain / Marilyn J. Siegel -- Head and neck / Marilyn J. Siegel -- Chest / Marilyn J. Siegel -- Breast / Ellen Chung and Marilyn J. Siegel -- Liver / Marilyn J. Siegel -- Gallbladder and biliary tract / Marilyn J. Siegel -- Spleen and peritoneal cavity / Marilyn J. Siegel -- Gastrointestinal tract / Marilyn J. Siegel -- Urinary tract / Marilyn J. Siegel -- Adrenal glands, pancreas, and other retroperitoneal structures / Marilyn J. Siegel and Ellen M. Chung -- Female pelvis / Marilyn J. Siegel -- Male genital tract / Brian D. Coley and Marilyn J. Siegel -- Musculoskeletal system and vascular imaging / Marilyn J. Siegel -- Spinal ultrasonography / Brian D. Coley and Marilyn J. Siegel -- Ultrasound-guided interventional procedures / Brian D. Coley.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Diagnostic ultrasonic imaging; Pediatric diagnostic imaging; Electronic books